POEM ANALYSIS CONDUCTED BY PROSPECTIVE TEACHERS OF TURKISH ON CAHIT SITKI TARANCI’S “CHILDHOOD” - Serdar DERMAN (Fırat University, 2020)
In this study, the analyzes of Turkish teacher candidates for the content of the poem “Childhood” of Cahit Sıtkı Tarancı, which is frequently included in Turkish textbooks, within the framework of the text-based teaching principle, which is the basic approach of Turkish teaching, was examined. Revealing the data about how Turkish teachers and prospective teachers make sense of the texts they can use in the lessons is of great importance in terms of both eliminating the problems in the teacher training process and planning the teaching. This qualitative descriptive study was carried out with 85 Turkish teacher candidates who took the Comprehension Techniques II: Listening Education course in the fall semester of the 2016-2017 academic year. The data were obtained through written answers to 4 questions addressed to students to analyze the text in question. The questions posed to prospective teachers within the scope of the research are as follows: 1. What does Affan Dede mean in the context of the poem named Childhood? 2. Explain the expression “sold me my childhood” according to the context of the poem. 3. What is childhood according to poetry? 4. What is the theme of poetry? Content analysis method was used to analyze the data collected from students. In the study, the opinions of the Turkish teacher candidates regarding the theme of the poem and the meaning of the expressions in the poem are presented in titles. As a result, it can be said that almost all of the Turkish teacher candidates are very successful in finding the theme of the poem, they can understand the concept of childhood as emphasized in the poem by Cahit Sıtkı Tarancı, and they understood the phrase “sold me, my childhood” correctly. In addition, Turkish teacher candidates were found to be unable to demonstrate the expected performance in interpreting the image of Affan Dede in poetry.